Sacral Sound-Engineering - BUDZYNSKI, Gustaw (Archives of Acoustics, 2011)
Organologic and campanologic acoustical problems due to applications to sacral objects are characterized on ground of numerous reviewed publications and engineering reports. Participation of several involved research centres, mostly Polish, at solving these problems is evaluated. Some desirable future developments are indicated. Appendices bring examples of documentation on selected investigated objects.